Multiple molecular mimics in Epstein Barr Nuclear Antigen-1, and the pathogenesis of multiple sclerosis - Fok Moon Lum; Neda Sattarnezhad; Peggy P. Ho; Noga Orr; William H. Robinson; Tobias V. Lanz; Lawrence Steinman (Proceedings of the National Academy of Sciences, 2026)
The Epstein–Barr virus (EBV) infects greater than 95% of humans and is associated with initiating and perpetuating multiple sclerosis (MS). Antibody to Epstein–Barr Nuclear Antigen-1 (EBNA1) is present in nearly 100% of patients with MS before the development of clinical symptoms. Infection with EBV is necessary, but not sufficient, for causation of disease. Within the EBNA1 transcription factor is a stretch of 47 amino acids containing three regions with shared linear sequences of portions of three molecules, Glialcell adhesion molecule (CAM), alpha Crystallin-B, and Anoctamin-2. These cross-reactive linear sequences between EBNA1 and each of these three molecules are termed “molecular mimics.” Cross-reactive adaptive immunity to these three molecules mimicking regions of EBNA1 each play distinct roles in the pathogenesis of MS. Antibodies to each of these molecules greatly increase the chance of developing MS. Analysis of the cellular landscape of MS lesions reveals EBNA1 in B cells, glial cells, and neurons. Here, we provide commentary on recent publications on the molecular and cellular landscape of EBV infection in studies on the blood, cerebrospinal fluid, and brain specimens of individuals with MS. The published studies reveal perspectives on the pathology of MS in detail ranging from the atomic level using crystallography to multiplexed anatomical imaging of lesions in the brain.